THE EFFECTIVENESS OF QUIZLET IN TEACHING VOCABULARY TO EFL STUDENTS TO ELEVENTH-GRADE STUDENTS AT SMA NEGERI 1 CIKANDE SERANG - Inti Aisyiyah; Fuad Abdul Baqi; Yuli Rohmiyati (Universitas Putera Batam, 2025)
This study examined the effectiveness of the Quizlet application in teaching vocabulary to eleventh-grade students at SMA Negeri 1 Cikande, Indonesia. The study addressed the persistent challenge of limited vocabulary mastery in English classrooms, where traditional teaching methods often dominate and technology integration remains minimal. Using a quantitative approach with a quasi-experimental design, two classes participated: the experimental group (n = 42) received vocabulary instruction through Quizlet, while the control group (n = 42) was taught using conventional methods. Both groups completed pre-tests and post-tests to measure vocabulary knowledge, including meaning, form, and usage. Statistical analyses, such as normality, homogeneity, and independent sample t-tests, were conducted using SPSS version 30. Results showed that the experimental group’s mean score increased from 54.64 to 83.57, while the control group improved from 66.43 to 75.60. Despite starting from a lower baseline, the experimental group achieved greater gains, indicating a significant difference (p < 0.05) between the two groups. These findings confirm the positive impact of Quizlet on students’ vocabulary learning. The study concludes that Quizlet proved to be an effective and engaging tool for improving students’ vocabulary mastery and recommends integrating Quizlet into English vocabulary instruction to enhance motivation and learning outcomes.